The radula of the extinct freshwater snail aylacostoma stigmaticum (caenogastropoda: Thiaridae) from Argentina and Paraguay - Vogler, Roberto Eugenio (2013)
The radular morphology of the extinct species Aylacostoma stigmaticum Hylton Scott, 1954 from Argentina and Paraguay is described for the first time from a dry syntype deposited in the La Plata Museum. The radula differed from those of the four Aylacostoma species for which anatomical data are currently available, in the presence and the number of basal cusps of the central tooth. This might be a useful character to differentiate species from Argentina, Paraguay and Brazil.